Strategies to Advance Women: Career Insights From Senior Leadership Women in Professional Sport in Canada - Amanda Cosentino; W. James Weese; Janelle E. Wells (Frontiers Media S.A., 2021)
Women remain minimally represented in senior leadership roles in sport, despite increased female participation in both sport, sport management education programs, and in entry levels positions in the industry. Many women prematurely exit mid-level leadership positions in sport, or are often overlooked for senior leadership positions. To uncover the experiences and strategies of women who made it through the process, we interviewed all the women (N = 7) who now hold senior leadership positions with professional sport properties in Canada. Participants revealed they overcame real and perceived barriers, and they suggested women seeking senior leadership roles in the industry: (a) find, and later become role models, mentors, and sponsors; (b) create access to networks and opportunities; (c) strategically self-promote, and; (d) purposefully build a varied career portfolio. Recommendations for the industry and all those who work in the industry are presented with a goal to break the cycle and help ensure more equitable and inclusive leaders in the senior leadership ranks.